Critical parameters determination and data exploratory analysis of rum aging process - García-Castellanos, Beatriz (2020)
Volume losses, known as wastage are presented during the rum aging process. As part of the continuous validation of the process Pareto Analysis is applied to determine the critical parameters that affect it. They are: aging time, volume, dioxygen concentration; temperature and humidity. The proper functioning of the process is influenced, among other factors, by the operation variables, which are recorded in databases. In this work, the databases were used to carry out a principal component analysis (PCA). The behavior of the main variables that affect the aging was understood, applying PCA, using the software The Unscrambler v10.4. With the ACP, the more important variables of the process were defined. The dimensionality was reduced to three main components that explain 89, 11 % of the total variance of the data, including the five variables. Wastages during 13 months were calculated (763.43 L). This value represents 10.5 % of the initial volume, higher than the 6 % recommended by the Dominican Republic Regulation, considered as a reference in this research. This wastage represents losses equivalent to $32 718. Losses that correspond to the 6 % of the initial volume were calculated ($18 631). If the process fulfils the Dominican regulation, $14 087 could be saved.